THE STUDENTS’ AWARENESS OF POLITENESS PRINCIPLES IN DAILY CONVERSATIONS: (A CASE STUDY IN ONE STATE UNIVERSITY IN BANTEN) - Anitawati Bachtiar (Jurnal Bebasan, 2014)
The understanding of native speakers’ culture is an important element that is related to manners and the use of words in the social interactions individually or collectively. Incomprehension and ignorance in using language will cause misunderstanding and may lead to physical or non-physical conflict. The aim of this research is to see the use of politeness principles in daily conversations on the case of English Debating Club in one state university in Banten. By using the theory of politeness principles of Paul Grice and Geoffrey Leech and collecting the data with the observation and in-depth interview toward the English as foreign language students in English Debating Club, this research shows that the words constructions from the utterances have obeyed the politeness principles maxims, such as tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and consideration maxim.